2021
DOI: 10.3389/fonc.2021.723753
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Serum tRF-31-U5YKFN8DYDZDD as a Novel Diagnostic Biomarker in Gastric Cancer (GC)

Abstract: BackgroundGastric cancer (GC) is one of the malignant tumors with the highest morbidity and mortality in the world. Early diagnosis combined with surgical treatment can significantly improve the prognosis of patients. Therefore, it is urgent to seek higher sensitivity and specificity biomarkers in GC. tRNA-derived small RNAs are a new non-coding small RNA that widely exists in tumor cells and body fluids. In this study, we explore the expression and biological significance of tRNA-derived small RNAs in GC.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The specific divergent primers involved in this paper were designed and synthesized by Ribobio Corporation (Suzhou, China), with the forward and reverse primer as shown in Table 1 . RT-qPCR was performed as described in previous studies ( Huang et al, 2021b ). In brief, the reaction was initiated at 95°C (10 min), followed by 40 cycles at 95°C (10s) and 62°C (34s) in the 20 ul system.…”
Section: Methodsmentioning
confidence: 99%
“…The specific divergent primers involved in this paper were designed and synthesized by Ribobio Corporation (Suzhou, China), with the forward and reverse primer as shown in Table 1 . RT-qPCR was performed as described in previous studies ( Huang et al, 2021b ). In brief, the reaction was initiated at 95°C (10 min), followed by 40 cycles at 95°C (10s) and 62°C (34s) in the 20 ul system.…”
Section: Methodsmentioning
confidence: 99%
“…Further validation revealed that tRF-GluTTC-027 could significantly regulate the related proteins in the MAPK signaling pathway and play a cancer suppressive role in GC progression [ 81 ]. Our research found that tRF-31-U5YKFN8DYDZDD and hsa_tsr016141 could be used as diagnostic and prognostic markers for GC, suggesting that tsRNAs could also be novel biomarkers for GC [ 82 , 83 ]. As a conclusion, tsRNAs can affect the proliferation and metastasis of GC and regulate the malignant progression of GC through multiple mechanisms.…”
Section: Dysregulation Of Tsrnas In Cancer and Related Rolesmentioning
confidence: 99%
“…On the serum side, the expression levels of hsa_tsr016141 and tRF-31-U5YKFN8DYDZDD were significantly increased in the serum of GC patients, which could effectively distinguish GC patients from normal controls and their expression levels were significantly decreased after GC surgery. Moreover, they were both good diagnostic markers and predictors of poor prognosis in GC [ 82 , 83 ]. Upregulated tRF-Leu-CAG in NSCLC serum was significantly associated with tumor progression, while tRF-Leu-CAG expression was similarly upregulated in NSCLC cell lines.…”
Section: Clinical Application Value Of Tsrnas In Cancer: As Biomarker...mentioning
confidence: 99%
“…Equally important were the findings of Huang et al. who found that tRF-31-U5YKFN8DYDZDD was highly upregulated in serum samples of gastric cancer (GC) patients ( 146 ). All these results denoted that circulating tsRNAs could be a potential non-invasive indicator of a cancer diagnosis.…”
Section: Biological Processes Correlated With Tsrnasmentioning
confidence: 99%